Study of CMOS power amplifier design techniques for ka-band applications - A.F Hasan; S.A. Z Murad; K.N Abdul Rani; F.A. Bakar; T.Z.A Zulkifli (Institute of Advanced Engineering and Science, 2019)
This paper reviews of high efficiency CMOS power amplifiers (PAs) in millimeter (mm) wave Ka - Band applications. The study is focused on the challenges in designing PA especially in GHz frequencies inclusive of high gain, good input and output matching, efficiency, linearity, low group delay and low power consumption. Several works on CMOS PA from year 2009 to 2018 are discussed in this paper. Recent developments of CMOS PAs are examined and a comparison of the performance criteria of various techniques is presented.